Research progress of kidney protection after hemorrhagic shock - LIU Jie, LI Jun, ZHANG Jingyu (精准医学杂志, 2024)
Hemorrhagic shock is a common acute and critical disease caused by trauma in clinic. In particular, local tissue hypoperfusion and cell hypoxia caused by renal ischemia and hypoxia can easily lead to acute kidney injury. In clinical practice, safer, practical, and effective resuscitation methods for patients with hemorrhagic shock are constantly explored to achieve the purpose of better protection of the kidney, such as the applications from colloidal crystal liquid to hypertonic fluid, from normal-pressure resuscitation to low-pressure resuscitation, from correcting blood pressure to restoring oxygen supply to tissue cells, from maintaining hemodynamic stability to inhibiting apoptosis, and from vasoactive drugs to Chinese traditional medicines to enzyme inhibitors. This article reviews the research progress of kidney protection for patients with hemorrhagic shock in recent years.